Bosnia and Herzegovina : Selected Economic Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This paper assesses the extent to which data unreliability could alter the assessment of the macroeconomic challenges ahead. The contributions of the indirect tax authority (ITA) in remedying the flaws are highlighted, and the architectural agenda is discussed. Fiscal sustainability and the government's bold initiatives to secure it by restructuring the domestic claims have been assessed and key implementation issues in realizing the government's plans noted. A survey of selected tax policy issues in Bosnia and Herzegovina is also included in the paper.